A combination of selenium and Bacillus subtilis improves the quality and flavor of meat and slaughter performance of broilers - Dong, Jihong; Qiu, Huiling; Gao, Shansong; Hou, Lele; Liu, Huawei; Zhu, Lianqin; Chen, Fu (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effects of the combination of selenium and Bacillus subtilis (Se-BS) on the quality and flavor of meat and slaughter performance of broilers. A total of 240 one-day-old Arbor Acres broilers were randomly allotted to four treatments of a basal diet supplemented with no selenium (control), sodium selenite (SS), BS, or Se-BS and raised for 42 days. Compared with the control group, Se-BS significantly increased the carcass weight, the half-eviscerated weight, the completely eviscerated weight, the carcass rate, and redness in broiler muscles; improved the antioxidant state by increasing glutathione peroxidase (GPx) and glutathione S-transferase activities, the total antioxidant capacity, and GPx-1 and thioredoxin reductase 1 messenger RNA (mRNA) levels; promoted biological activity by increasing the contents of glutamate, phenylalanine, lysine, and tyrosine; and increased Se and five types of nitrogenous volatile substances in muscles. On the other hand, Se-BS treatment decreased the shear force, drip loss, and the malondialdehyde, glutathione, and lead contents in muscles. Se-BS exerted a better effect on slaughter performance, the physicochemical quality of meat, the redox status, the amino acid contents, the trace element contents, and volatile substances compared with SS and BS. In conclusion, Se-BS had a positive effect on the quality and flavor of meat and slaughter performance of broilers, suggesting that Se-BS may be a beneficial feed additive.